Collaborating and learning a second language in a Wireless Virtual Reality Environment. (15th October 2008) - Garcia-Ruiz, Miguel A.; Edwards, Arthur; El-Seoud, Samir A.; Aquino-Santos, Raul
Virtual Reality (VR), a computer-generated 3D space that is multisensorial, interactive and engaging, is today one of the new frontiers in Computer-Assisted Language Learning (CALL). VR can be used to promote language learning and practice as it simulates reality, while offering a stimuli-rich environment for language students. The purpose of this paper is twofold: To provide an introduction to VR applications in CALL, and to describe the implementation of a Collaborative Virtual Reality Environment (CVRE) running on a wireless network, which is currently being assessed by Mexican Engineering students for listening comprehension practice of the English language.